Petticoat Detective - Brownley, Margaret (Brownley, Margaret. Undercover ladies., 2014)
Pinkerton detective Jennifer Layne is no stranger to undercover work. But posing as a lady companion named Amy at Miss Lillian's Parlor House and Boots is a first for her. She's finally landed a high-profile case and is on the trail of the notorious Gunnysack Bandit, when one of Miss Lillian's girls essential to her investigation meets an untimely demise. Only a handful of people are in the house at the time of her death, including handsome Tom Colton, a former Texas Ranger determined to clear his brother's name. Amy has many reasons to suspect Tom of murder-and one very personal reason to hop.